Reduction of the «edge effect» of Electrodes in the Contact Boundary with the Dielectric - T. I. Shahtakhtinskiy (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
It is shown that when the diameters of flat-parallel electrodes with sharedges match the diameter of a cylindrical dielectric between them, the «edgeffect» is reduced.